(untitled) (International conference on multidisciplinary science, 2025)
This research explores the concept of "Motherland" in Uzbek and English cultures, focusing on its linguistic, cultural, and emotional significance. By comparing expressions, idioms, and cultural values associated with the term, the study identifies similarities and differences in how the idea of the motherland is perceived in both languages. The findings contribute to a deeper understanding of national identity and cultural worldview in a comparative linguistic context.